2008
DOI: 10.1016/j.ccr.2008.10.005
|View full text |Cite
|
Sign up to set email alerts
|

miR-296 Regulates Growth Factor Receptor Overexpression in Angiogenic Endothelial Cells

Abstract: SUMMARY A key step in angiogenesis is the upregulation of growth factor receptors on endothelial cells. Here we demonstrate that a small regulatory microRNA, miR-296 has a major role in this process. Glioma cells and angiogenic growth factors elevate the level of miR-296 in primary human brain microvascular endothelial cells in culture. The miR-296 level is also elevated in primary tumor endothelial cells isolated from human brain tumors compared to normal brain endothelial cells. Growth factor-induced miR-296… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
332
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(344 citation statements)
references
References 48 publications
10
332
1
1
Order By: Relevance
“…The expression of miR‐296 induces angiogenesis in vascular disease and cancer 95, 96. A study showed that glioma or growth factor‐mediated miR‐296 in ECs leads to enhanced levels of pro‐angiogenic growth factor receptors.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of miR‐296 induces angiogenesis in vascular disease and cancer 95, 96. A study showed that glioma or growth factor‐mediated miR‐296 in ECs leads to enhanced levels of pro‐angiogenic growth factor receptors.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…A study showed that glioma or growth factor‐mediated miR‐296 in ECs leads to enhanced levels of pro‐angiogenic growth factor receptors. Growth factor‐induced miR‐296 significantly enhances angiogenesis directly via reducing hepatocyte growth factor‐regulated tyrosine kinase substrate (HGS), thereby increasing VEGFR2 and platelet‐derived growth factor receptor‐β (PDGFR‐β) and inhibiting DLL4 and Notch1 95, 96. Additionally, the results have an effect on improving the expression of VEGF.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…2A, i-iii; Â2), suggesting increased intratumor pressure, possibly caused by high permeability of the tumor vessels (Fig. 1B) and poor lymphatic drainage (26,27).…”
Section: Imaging Tumor Vascular Response To Antiangiogenic Therapiesmentioning
confidence: 99%
“…miR‐296 is an angiomiR that has been found to be upregulated in endothelial cells with the presence of glioma cells or angiogenic growth factors such as VEGF. Augmented expression of miR‐296 is associated with increased endothelial cell tube formation and enhanced vascularization of tumors, while knockdown of miR‐296 results in reduced tumor angiogenesis 79.…”
Section: Introductionmentioning
confidence: 99%